2017
DOI: 10.2116/analsci.33.307
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Control of Bioluminescence by Blocking the Adsorption of the Bacterial Luciferase Using a Mercaptobipyridine Self-assembled Monolayer

Abstract: An N-butyl-N′-(4-mercaptobutyl)-4,4′-bipyridinium (4BMBP) was modified on a gold electrode to improve the electrochemical control of the bacterial luciferase (BL) luminescence system. The 4BMBP-modified gold electrode (4BMBP/Au) was able to prevent the adsorption of BL on the electrode surface, and enhanced the electrochemical regeneration rate of the reduced flavin mononucleotide (FMNH2), which is one of the substrates of the BL luminescence reaction. By using the 4BMBP/Au, the luminescence intensity increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Cluc catalyzes oxidation of the luciferin to produce light emission without requiring ATP to be the same as bacteria luciferase. 14 The recombinant Cluc protein has 30 lysine residues, except for the signal peptide at the N-terminal. We incubated the reagent NHS-PEG8-maleimide with Cluc at 4 C for 2 h. After removing the excess amount of the reagent, we measured the remaining activity of Cluc by mixing the luciferin.…”
Section: Resultsmentioning
confidence: 99%
“…Cluc catalyzes oxidation of the luciferin to produce light emission without requiring ATP to be the same as bacteria luciferase. 14 The recombinant Cluc protein has 30 lysine residues, except for the signal peptide at the N-terminal. We incubated the reagent NHS-PEG8-maleimide with Cluc at 4 C for 2 h. After removing the excess amount of the reagent, we measured the remaining activity of Cluc by mixing the luciferin.…”
Section: Resultsmentioning
confidence: 99%
“…2−5 Yamasaki et al controlled the bioluminescence of bacteria by blocking the adsorption of luciferase with electrochemical methods; moreover, they proved that luciferase had specific electrochemical stability. 6 Liu et al found that by calculating the energetics, charge transfer, electronic structures, and molecular dynamics by using reliable density functional theory (DFT) and time-dependent DFT principles, a molecule with a luciferase structure could achieve over 43% quantum yield of the light emitter. 2 A multicolor organic light emitting device (OLED) assembled by amino oxyluciferin was developed by Min et al 7 The bioluminescence reaction from fireflies is shown in Figure 1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The light from fireflies is generated from a molecule named luciferase . In recent research, these extraordinary molecules with high energy transfer have been used in electrochemical devices. Yamasaki et al controlled the bioluminescence of bacteria by blocking the adsorption of luciferase with electrochemical methods; moreover, they proved that luciferase had specific electrochemical stability . Liu et al found that by calculating the energetics, charge transfer, electronic structures, and molecular dynamics by using reliable density functional theory (DFT) and time-dependent DFT principles, a molecule with a luciferase structure could achieve over 43% quantum yield of the light emitter .…”
Section: Introductionmentioning
confidence: 99%